Modelo de Gestión del Talento Humano para el fortalecimiento del desempeño laboral de los trabajadores de Sanbel Flowers Cia. Ltda. - Sánchez Grandes, Andrea Teresa (2020)
The Management of Human Talent is perhaps the fundamental aspect in the administration of any organization, it is for this reason that Sanbel Flowers considered the opportunity to apply an investigation around the management of the personnel that the company has. First, it was exploratively determined that there are shortcomings in the processes inherent to Human Talent, which is evidenced in the introduction, which describes the main problems around the subject, as well as the objectives set; in the same way, GTH is currently analyzed in a macro, meso and micro context. Chapter 1 is structured based on three relevant aspects, research background, epistemological foundation and the state of the art. The investigative background contributes to the understanding of how other companies with a similar activity have effectively managed their Human Talent; in the same way, the epistemological foundation contributes to describe concepts, basically about GTH, specific models and work performance; finally the state of the art explains the innovations or updated studies that generate a better use of all the tools for the management of personnel. In Chapter 2, the proposal has been developed, which is based on the Human Talent Management by Competencies model, a model that was chosen for its versatility and flexibility at the time of its application. To achieve this, it was necessary to apply a fieldwork methodology, by applying surveys to the company's internal and external customers, and from which more precise data was obtained regarding the existing problems. The research and subsequent proposal constitute a clear guide on the xi premises that must be applied in all tasks concerning the GTH department. Finally, chapter 3 details the endorsement made by an expert on the subject and the person who will use the proposal within the company. In both cases, it coincides in the fact that the material generated has high relevance, utility and long-term applicability, which is why they consider it a valuable contribution to Sanbel Flowers